The Relationship between Self-Efficacy and the Level of Anxiety of Students Working on Their Thesis - Herliana Sabila Putri; Ira Ocktavia Siagian; Herwinda Sinaga (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2024)
Introduction: A thesis is a graduation requirement for students, which can lead to feelings of anxiety. Approximately 80% of students working on their thesis experience anxiety. The various obstacles encountered during the thesis process create stress, leading to increased anxiety among students. The anxiety experienced by final-year students impacts their level of self-efficacy. Objectives: This study aims to determine the relationship between self-efficacy and levels of anxiety among students working on their thesis at Institut Kesehatan Immanuel. Methods: This research employs a quantitative descriptive correlational approach with a cross-sectional design. The sample was selected using probability sampling techniques, involving 120 respondents. The measurement tools used were the General Self-Efficacy Scale (GSES) and the Zung Self-Rating Anxiety Scale (ZSAS) Results: The results indicated that 59% of students had high self-efficacy, while 61% experienced moderate anxiety. The correlation between self-efficacy and anxiety levels was analyzed using Spearman's correlation test, with a significance value of 0.000 (p<a) and a correlation coefficient of -0.606, indicating a strong negative relationship. This identifies that lower anxiety is associated with higher self-efficacy. Discussion: This research could serve as input for institutions, especially department heads, to develop self-development programs that can be incorporated into each course, and to provide counseling guidance to reduce the anxiety levels of students working on their theses.